Application of liquid biopsy in lung cancer management - Shraddhanjali Satapathy; Balamurugan Thirunavukkarasu; Deepali Jain (Wolters Kluwer Medknow Publications, 2024)
Current advances in the understanding of the lung cancer landscape have drastically changed the approach to treating a patient with lung carcinoma. The field has progressed from analyzing single gene to using advanced techniques like next-generation sequencing and microarray technology. While a tumor tissue sample is considered the gold standard, it has several limitations. The limitations of invasive procedures, long processing periods, inaccessibility, and sample inadequacy are being addressed by sampling biofluids, termed 'liquid biopsy,' which offers a less invasive and more accessible way to obtain tumor-related information. Liquid biopsy has transformed the care of lung cancer patients by directly targeting somatic alterations from tumors. This article provides insights into the biology, technical aspects, limitations, and practical applications of 'liquid biopsy,' focusing on cell-free DNA and circulating tumor DNA in the context of lung cancer.